Earth Observation Data Cubes - Camara, Gilberto (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Satellite Earth observation (EO) data have already exceeded the petabyte scale and are increasingly freely and openly available from different data providers. This poses a number of issues in terms of volume (e.g., data volumes have increased 10